STUDY OF THE FUNCTIONALITY OF A NOVEL SOLUTION BINDER OBTAINED FROM OCIMUM BASILICUM SEEDS: A MECHANISTIC APPROACH - HARDIKAR, SHARWAREE R.; JAMDADE, NILESH S. (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of the present study was to investigate the functionality of the hydrogel isolated from the seeds of Ocimum basilicum (Gel) as a novel solution binder. Methods: Paracetamol is known to possess poor manufacturability. Therefore it was selected as a model drug to study the efficiency of Gel as a solution binder. Paracetamol tablets were prepared at gradually increasing compression pressure from the granules prepared by using Gel of various viscosities as a solution binder. Compactibility parameter was calculated to assess the utility of Gel as a novel tablet binder. Optimization of the formulation was done by adopting factorial design as an appropriate DOE. Tablets of factorial batches were evaluated for disintegration time and crushing strength. The effect of viscosity of binder solution used to prepare granulation and compression pressure applied on granulation on the performance of the tablets was confirmed by analyzing the data using ANOVA. Results: The addition of binder solution to prepare granulation with the viscosity ≥ 19.33 centipoises was found to be suitable to attain desired degree of agglomeration. The crushing strength of the tablets was found to be increased with an increase in compression pressure and an increase in viscosity of binder solution. Conclusion: The compatibility parameter was observed to be increased as the viscosity of the binder solution added in the formulation was gradually increased. The Gel as a binder material was found to deform plastically at compression pressures 34.48 to 75.85 MPa. This confirmed its functionality as a solution binder in Paracetamol tablet preparation.